The influence of catalyst on the characteristics of biodiesel from waste cooking oil - Muhammad Idris; Tony Siagian; Dedy Sofyanto; Putri Rizky; Friska Heriyanti; Derlini; Imam Azhari; Zakir Husin (JTTM : Jurnal Terapan Teknik Mesin, 2023)
The aim of this research was to investigate the influence of catalyst on the flash point, viscosity, density, and iodine value of biodiesel. The raw material used in biodiesel production was waste cooking oil. The transesterification process was employed by reacting the catalyst and methanol, followed by mixing them with the waste cooking oil simultaneously. The catalyst concentration variations used in this study were 0.25% and 0.5%. The resulting transesterification mixture was left to settle for approximately 10 minutes. The biodiesel and glycerol were separated after settling, and the biodiesel was washed with distilled water at a temperature of 50°C and then evaporated at 100°C. The flash point test results for catalyst concentrations of 0.25% and 0.5% were 58°C and 48.5°C, respectively. The viscosity test results for catalyst concentrations of 0.25% and 0.5% were 4.567 x 10-6 m2/s and 4.625 x 10-6 m2/s, respectively. The density test results for catalyst concentrations of 0.25% and 0.5% were 889 kg/m3 and 888.3 kg/m3, respectively. The iodine value test results for catalyst concentrations of 0.25% and 0.5% were 112.2 g I2/100g and 114 g I2/100g, respectively. Based on the test data, the flash point, viscosity, density, and iodine value were obtained. The test results indicated that the flash point values from both experiments did not meet the biodiesel quality standards. However, the viscosity and density test results from both experiments met the biodiesel quality standards and were suitable for use. Regarding the iodine value test, the characteristics of the biodiesel from both experiments did not fully meet the biodiesel standard, although the results obtained were not significantly different from the quality standards set by the Ministry of Energy and Mineral Resources